We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+3
1161
3
avatar+1904 

\(\sqrt\frac{5}{x+3}=\frac{4}{x+\sqrt4}\)

 

 

Please show how you got to your answer.

 Jan 16, 2016

Best Answer 

 #3
avatar+104712 
+15

 sqrt [(5) / (x + 3)]  = 4 / [x + sqrt(4)]        

 

 sqrt [ (5) / (x + 3)]  = 4/ [x + 2]           square both sides

 

5  / [x + 3]  =   16/ [x^2 + 4x + 4]         cross-multiply

 

5 [ x^2 + 4x + 4 ]  = 16[x + 3]     simplify

 

5x^2 + 20x + 20  = 16x + 48 

 

5x^2 + 4x -28  =  0     factor

 

[5x  + 14] [ x - 2]  = 0     

 

Setting each factor to O  we have that x = -14/5   or x = 2

 

However.....x = -14/5  produces a negative quantity on the right hand side of the original equation, and we can never get a negative out of the left hand side......so.......the two sides would have unequal signs, so x = -14/5  is not a soluition

 

So.......x = 2   is the only solution.....

 

 

 

cool cool cool

 Jan 16, 2016
 #1
avatar+4080 
+5

That problem should be illegal...

 Jan 16, 2016
 #2
avatar
+10

Solve for x:
sqrt(5) sqrt(1/(x+3)) = 4/(x+2)

Cross multiply:
sqrt(5) sqrt(1/(x+3)) (x+2) = 4

Divide both sides by sqrt(5):
sqrt(1/(x+3)) (x+2) = 4/sqrt(5)

Divide both sides by x+2:
sqrt(1/(x+3)) = 4/(sqrt(5) (x+2))

Raise both sides to the power of two:
1/(x+3) = 16/(5 (x+2)^2)

Take the reciprocal of both sides:
x+3 = 5/16 (x+2)^2

Expand out terms of the right hand side:
x+3 = (5 x^2)/16+(5 x)/4+5/4

Subtract (5 x^2)/16+(5 x)/4+5/4 from both sides:
-(5 x^2)/16-x/4+7/4 = 0

The left hand side factors into a product with four terms:
-1/16 ((x-2) (5 x+14)) = 0

Multiply both sides by -16:
(x-2) (5 x+14) = 0

Split into two equations:
x-2 = 0 or 5 x+14 = 0

Add 2 to both sides:
x = 2 or 5 x+14 = 0

Subtract 14 from both sides:
x = 2 or 5 x = -14

Divide both sides by 5:
x = 2 or x = -14/5

sqrt(5) sqrt(1/(x+3)) => sqrt(5) sqrt(1/(3-14/5))  =  5
4/(x+2) => 4/(2-14/5)  =  -5:
So this solution is incorrect

sqrt(5) sqrt(1/(x+3)) => sqrt(5) sqrt(1/(3+2))  =  1
4/(x+2) => 4/(2+2)  =  1:
So this solution is correct

The solution is:
Answer: | x = 2

 Jan 16, 2016
 #3
avatar+104712 
+15
Best Answer

 sqrt [(5) / (x + 3)]  = 4 / [x + sqrt(4)]        

 

 sqrt [ (5) / (x + 3)]  = 4/ [x + 2]           square both sides

 

5  / [x + 3]  =   16/ [x^2 + 4x + 4]         cross-multiply

 

5 [ x^2 + 4x + 4 ]  = 16[x + 3]     simplify

 

5x^2 + 20x + 20  = 16x + 48 

 

5x^2 + 4x -28  =  0     factor

 

[5x  + 14] [ x - 2]  = 0     

 

Setting each factor to O  we have that x = -14/5   or x = 2

 

However.....x = -14/5  produces a negative quantity on the right hand side of the original equation, and we can never get a negative out of the left hand side......so.......the two sides would have unequal signs, so x = -14/5  is not a soluition

 

So.......x = 2   is the only solution.....

 

 

 

cool cool cool

CPhill Jan 16, 2016

30 Online Users

avatar